Effect of calcium sulfate variety and content on hydration mechanism of grout sealants for coal-bed methane drainage boreholes. (10th April 2019) - Bi, Ruiqing; Cheng, Wuyi; Chen, Xuexi
Highlights: Hydration heat, in situ dynamic resistivity, morphology, XRD, and TG-DSC were used. Unusual pompon spherulites of ettringite were formed. The eluted ions for the displacement precipitation on the C4 A3 skeleton. Dissolution rate of C4 A3 skeleton decreased with the increasing formation rate of AFt. Abstract: Few studies have been reported on grout sealants for coal-bed methane drainage boreholes prepared with high water-to-cement (w/c) ratios approaching 1, particularly calcium-sulfoaluminate (CSA)-type cementitious grout sealants. Thus, this study investigated the effects of the calcium sulfate variety and content on the hydration process and microstructural features of grout sealants for coal-bed methane drainage boreholes. The cube strength, hydration exothermicity, in situ dynamic resistivity, and microscopic morphology were examined, and X-ray diffraction, and thermogravimetry–differential scanning calorimetry were conducted. Pompon spherulites of ettringite, which is a different morphology from that of most cementitious materials, were observed. The resistivity measurement were more suitable for analysing the hydration process than the hydration heat analysis. The hydration of CaSO4 produced a low pH in high-gypsum-content grouts; therefore, using a relatively low calcium sulfate content could produce a high pH, which would benefit the hydration reaction while simultaneously decreasing the possibility of the ye'elimite (C4 A3 ) skeleton forming ettringite owing to its contact with Al 3+ and SO4 2− . The dissolution rate of the C4 A3 skeleton decreased with the increasing rate of ettringite precipitation. The increases in the Al–O octahedral nucleation barrier and in the critical size of the nucleus resulted in a low ettringite nucleation rate.